PELAKSANAAN PUNGUTAN PAJAK BUMI DAN BANGUNAN BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAN RETRIBUSI DAERAH ( STUDI DI KABUPATEN INDARAGIRI HILIR) - Muhsin (JURNAL HUKUM DAS SOLLEN, 2017)
Tax is the contribution of the people to the State treasury under the Act, by not receiving lead services (kontraprestasi) that can be directly demonstrated and used to pay public expenditure. All types of levies and taxes must be based on legislation "and that," Non-statutory charges should be avoided to avoid high-cost economies and burden the public ". This mandate is actually an emphasis from article 23 of the 1945 Constitution. These sources of revenue are very petning to run the activities of each level of government, because without adequate receipts then the government programs will not run optimally, tax levies earth and buildings in each District is one of the important regional financial support for the sustainability of the government in the area, especially in Indragiri Hilir Regency